UNDERMINING DEMOCRACY AND NATIONAL SECURITY: PUBLIC POLICY AND COVERT ACTIONS OF THE U.S. IN GREECE DURING THE COLD WAR - Spasojević, Dušan (Serbian political thought, 2025)
The subject of this paper is the political penetration of the United States into Greece during the Cold War, with a particular emphasis on the role and position of the Greek military in this process. The aim of the study is to explore, describe, and explain the causes, modus operandi, and consequences of the manipulation of the political systems of smaller countries by great powers, particularly from the perspective of their subjugation, dependency, and incorporation into an international order based on the division of spheres of influence. The paper examines this phenomenon through a synthesis of theoretical concepts from international politics and civil-military relations as the most significant institutional component of defence policy and a crucial aspect of national security policy, utilising methods of qualitative analysis, triangulation, and process tracing through the case study methodology. The research findings indicate that the armed forces and the Central Intelligence Service of Greece, as targets of US political penetration, became key instruments for maintaining an undemocratic order through political interference and reduced combat readiness in favour of US foreign policy goals. The conclusions underline the importance of strengthening institutional capacities as essential conditions for defending national sovereignty and democracy.